Cerium Oxide Nanoparticles Ameliorate Oxidative Stress, Inflammation, and Pain Behavior in Neuropathic Rats - Forouzanfar, Fatemeh; Pourbagher-Shahri, Ali M.; Darroudi, Majid; Sadeghi, Mahmood; Vafaee, Farzaneh; Moghadam, Omid Fakharzadeh; Mashhad, Negar Moghaddas; Ghazavi, Hamed; Khorrami, Mohammad Bagher (Current Neurovascular Research, 2023)
Background: Neuropathic pain originating from a dysfunction in the nervous system is often intractable and chronic. Recently, several studies using nanoparticles suggested a new way to control neuropathic pain. This study intended to explore the potential neuroprotective effect of Cerium Oxide Nanoparticles (CNPs) synthesized by pullulan in neuropathic pain in rats. Methods: On the right common sciatic nerve of male Wistar rats, the chronic constriction injury (CCI) procedure was used to establish a neuropathic pain model. CNPs were injected into the caudal vein of the rat. Behavioral methods were used to detect mechanical allodynia, cold allodynia, and thermal hyperalgesia in rats. Besides, inflammation factors, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, nitric oxide (NO), and markers of oxidative stress, including Malondialdehyde (MDA) and total thiol, were measured in the spinal cord segment of rats. Results: In rats with CCI, mechanical allodynia, cold allodynia, and thermal hyperalgesia developed, which improved when the rats were administered CNPs. Spinal cord specimens of CCI rats had elevated inflammation and oxidative stress status (↑IL-1β, ↑TNF-α, ↑NO, ↑MDA) and decreased antioxidative levels (↓total thiol). As a result of CNPs treatment, these changes were reversed in the spinal cord specimens. Conclusion: CNPs alleviate neuropathic pain by exhibiting antioxidative and anti-inflammatory activities.
Keywords: neuroinflammation